Appendix neuroendocrine tumor: A rare incidental histopathological finding after perforated appendicitis procedure (Research, Society and Development, 2021)
Introduction: Appendix neoplasms are rare and identified in about 1% of all appendectomies, with the most common etiologies being first of epithelial origin and second, neuroendocrine. Neuroendocrine tumors are derived from enterochromaffin cells, producing the granules Chromogranin A and Synaptophysin and are the second most common histological type of appendix neoplasm, often found incidentally after appendectomy due to their indolent presentation, but are sometimes the causes of acute appendicitis. Objective: To report the experience of a patient diagnosed with neuroendocrine tumor of the appendix after acute perforated appendicitis who had previously presented abdominal vessel thrombosis. Case report: Male patient, 28 years old, with abdominal pain in mesogastrium and epigastrium for 2 months, being initially diagnosed with intra-abdominal thrombosis. Hospitalized presenting a diffuse abdominal pain, more prominent in the right iliac fossa with painful decompression, submitted to exploratory laparoscopy and evidenced grade 4 appendicitis. Histopathological analysis revealed a differentiated neuroendocrine tumor in appendage G1 with a size of 2 mm, mitotic index with less than 2 mitoses, pT1 pNx pathological staging, free margins, lymphovascular and perineural invasion. Immunohistochemistry with cell proliferation index (Ki-67) of 1% and identification of the components Chromogranin A polyclonal clone and Synaptophysin clone DARKSYNAP positive. Conclusion: We report a case of a patient with Neuroendocrine Tumor of the appendix with initial presentation as acute appendicitis and, to the pathology, limited to the appendix without lymphovascular invasion, with total appendectomy as a curative procedure.